Producing Idols: Understanding Chinese Idol Development Since 2018 Through the Lens of Chuang 2021 - Li, Qiting (My University, 2025)
This thesis provides a China’s localization perspective in understanding the idol phenomenon, an increasingly prominent aspect of entertainment culture internationally. It also examines the evolution of media and socio-cultural transitions in China. Through a historical review on the transitions of Chinese media landscape and semantic changes of idols, the thesis argues that the role of idols in China has undergone a transformation from socialist role models to commercial media celebrities, while the rapid growth of the Internet industry has fueled the rise of Chinese idols. Before examining idols in a Chinese social context, this study first discusses the general characteristics of idols as entertainment professionals. As a highly commercialized form of youth culture, idols engage in transmedia participation led by variety shows to showcasing their selling points of personality, and aim heavily to establish strong parasocial relationships with their fans. In this study, the Chinese idol–fan relationship is situated and explained through the theory of parasocial phenomena. The phenomenon of local idols creating a craze in China had been triggered by the idol competition shows produced by Chinese streaming platforms since 2018. By conducting thematic analysis on the show Chuang 2021, this study identifies five key features of online idols producing programs. These include the intensive fan engagement; the consumer behaviors tied to a high degree of platformization; show content characterized by entertainment value and relatability to everyday life; and the emphasis on Chinese culture in a cross-cultural context. In the process of show-viewing, the spectators are guided to experience romantic parasocial relationships; parasocial friendships; the sense of idol–fan having a shared dream and destiny; and as being defenders of Chinese culture together with their idols. The localization practices of Chinese online idol competition show reflect to the constraints and driving factors of the development of Chinese idols, and the ways in shaping the idol fan culture in China.
Keywords: Chinese idols, personality, online idol competition show, parasocial relationships, platformization, cultural confidence